Prospective pilot trial of PerMIT versus standard anticoagulation service management of patients initiating oral anticoagulation - Borgman, Mark P.; Pendleton, Robert C.; McMillin, Gwendolyn A.; Reynolds, Kristen K.; Vazquez, Sara; Freeman, Andrew; Wilson, Andrew; Valdes, Roland, Jr.; Linder, Mark W. (Thrombosis and Haemostasis, 2012)
We performed a randomised pilot trial of PerMIT, a novel decision support tool for genotype-based warfarin initiation and maintenance dosing, to assess its efficacy for improving warfarin management. We prospectively studied 26 subjects to compare PerMIT-guided management with routine anticoagulation service management. CYP2C9 and VKORC1 genotype results for 13 subjects randomly assigned to the PerMIT arm were recorded within 24 hours of enrolment. To aid in INR interpretation, PerMIT calculates estimated loading and maintenance doses based on a patient’s genetic and clinical characteristics and displays calculated S-warfarin plasma concentrations based on planned or administered dosages. In comparison to control subjects, patients in the PerMIT study arm demonstrated a 3.6-day decrease in the time to reach a stabilised INR within the target therapeutic range (4.7 vs. 8.3 days, p = 0.015); a 12.8% increase in time spent within the therapeutic interval over the first 25 days of therapy (64.3% vs. 55.3%, p = 0.180); and a 32.9% decrease in the frequency of warfarin dose adjustments per INR measurement (38.3% vs. 57.1%, p = 0.007). Serial measurements of plasma S-warfarin concentrations were also obtained to prospectively evaluate the accuracy of the pharmacokinetic model during induction therapy. The PerMIT S-warfarin plasma concentration model estimated 62.8% of concentrations within 0.15 mg/l. These pilot data suggest that the PerMIT method and its incorporation of genotype/phenotype information may help practitioners increase the safety, efficacy, and efficiency of warfarin therapeutic management.Clinical Trials Registration identifier: NCT00993200
Keywords: Anticoagulation; warfarin; pharmacogenetics; algorithm; clinical trial